2022
DOI: 10.3390/plants11070935
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Promotes Adventitious Root Development in Cucumber under Salt Stress by Enhancing Antioxidant Ability

Abstract: As a gas signal molecule, hydrogen sulfide (H2S) can enhance plant stress resistance. Here, cucumber (Cucumis sativus ‘Xinchun NO. 4’) explants were used to investigate the role of H2S in adventitious root development under salt stress. The results show that sodium chloride (NaCl) at 10 mM produced moderate salt stress. The 100 µM sodium hydrosulfide (NaHS) treatment, a H2S donor, increased root number and root length by 38.37% and 66.75%, respectively, indicating that H2S effectively promoted the occurrence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 47 publications
(51 reference statements)
1
19
0
Order By: Relevance
“…Our previous study found that NO or H 2 O 2 treatment enhanced POD activity in chrysanthemum cuttings during AR initiation [ 19 ]. Sodium hydrosulfide (NaHS) treatment increased the activities of antioxidant enzymes (POD, superoxide dismutase, ascorbate peroxidase and catalase) and increased the contents of ascorbic acid and glutathione during rooting [ 54 ]. In this study, MRW, EBL and MRW + EBL treatments significantly enhanced POD activity during both the initiation phase (6-12 h) and expression phase (12-48 h), while Brz treatment significantly inhibited the positive effect (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study found that NO or H 2 O 2 treatment enhanced POD activity in chrysanthemum cuttings during AR initiation [ 19 ]. Sodium hydrosulfide (NaHS) treatment increased the activities of antioxidant enzymes (POD, superoxide dismutase, ascorbate peroxidase and catalase) and increased the contents of ascorbic acid and glutathione during rooting [ 54 ]. In this study, MRW, EBL and MRW + EBL treatments significantly enhanced POD activity during both the initiation phase (6-12 h) and expression phase (12-48 h), while Brz treatment significantly inhibited the positive effect (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our results implied that suitable concentration of NO might alleviate the negative effect of Cd stress on the adventitious rooting of cucumber. Moreover, several studies indicated that NO could regulate the growth and development of plant roots, including root elongation, lateral root growth and adventitious root formation ( Díaz et al., 2021 ; Wang et al., 2021 ; Liu Y.Y. et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mixture is heated in a boiling water bath for 30 min and then centrifuged for 10 min. The absorbance of the supernatant was measured at 450 nm, 532 nm and 600 nm ( Liu et al, 2022b ). For estimating generation, the samples were homogenized with potassium phosphate buffer (pH 7.8) and centrifuged for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…However, the related genes in the POD activity were partially downregulated due to the prolonged NaCl stress. APX, GPX, and GR are important enzymes for scavenging intracellular ROS [ 68 ].…”
Section: Discussionmentioning
confidence: 99%